Validating the Hebrew version of the Person‐Centered Care of Older People with Cognitive Impairment in Acute Care scale. (18th November 2020) - Werner, Perla; AboJabel, Hanan; Cohen Saban, Hagar; Kermel Schiffman, Ile; Idilbi, Nasra; Engel, Anat; Malka‐Zeevi, Helena; Dwolatzky, Tzvi; Dudkiewicz, Mickey
Abstract: Aim: To validate the Hebrew version of the Person‐Centered Care of Older People with Cognitive Impairment in the Acute Care scale. Background: The Person‐Centered Care of Older People with Cognitive Impairment in Acute Care scale is a reliable and valid measure to assess the extent to which person‐centred care among people with dementia is adopted in the acute care setting. Methods: A cross‐sectional study using a self‐reporting structured questionnaire was conducted with 678 professionals (69% nurses, 26% physicians, 5% other health care professionals) in five hospitals across Israel. Results: Similar to other languages, best results were obtained using 14 of the 15 items included in the original scale. Confirmatory factor analysis indicated the appropriateness of a three‐factor structure for the Hebrew version of the scale. Cronbach's alpha scores for these factors were moderate to good. Conclusions: The Hebrew version of the scale is a reliable and valid tool for assessing hospital professionals' perceptions of person‐centred care. Implications for Nursing Management: A new language validated version of the scale will allow nurse managers to learn from multiple countries' experience while conducting international comparisons. Such developments will improve and expand the implementation of the person‐centred care among people with dementia in hospital settings.